Management of stage 1 renal cell cancer in patients immunosuppressed for organ transplantation or autoimmune disease - Ghasemzadeh, Ali; Wendt, Eric T.; Dolan, Brendan; Craig, Juliana; Allen, Glenn O.; Abel, E. Jason; Shapiro, Daniel D. (Frontiers in Urology, 2023)
To describe the treatment and outcomes of patients who are medically immunosuppressed due to prior organ transplantation or autoimmune disease with clinical T1 renal cell carcinoma (cT1). Methods An institutional database of patients treated for RCC was queried for patients with cT1 RCC and on chronic medical immunosuppression at the time of RCC diagnosis. Outcomes for patients undergoing 1) surgery 2) ablation or 3) active surveillance (AS) are described.Between 2010-2022, 74 medically immunosuppressed patients with RCC were identified who were treated with surgery (n=29), ablation (n=33), or AS (n=12). Seven (58%) AS patients underwent deferred treatment (6 ablations, 1 nephrectomy) due to tumor growth. Comparing surgery and ablation patients, the 30-day readmission rate (17% vs 9%, p=0.7) and 90-day complication rate (24% vs 21%, p=0.9) were similar, respectively. One (3%) surgical and 2 (6%) ablation patients recurred locally. Despite being immunosuppressed, only 1 (3%) surgical, 1 (3%) ablation, and no AS patients progressed to metastatic disease. No significant differences were noted for the local recurrence-free, metastasis-free, and overall survival for the 3 cohorts (P>0.05 for all).Patients with stage one RCC with medical immunosuppression can be safely managed with surgery, thermal ablation or active surveillance with similar outcomes to historical series of nonimmunosuppressed patients. Future prospective studies should investigate shared decision making in this patient cohort and should include discussion of less aggressive options that minimize morbidity but preserve oncologic control.